A Novel Cast Aluminum Joint for Reticulated Shell Structures: Experimental Study and Modeling. Issue 6 (June 2013) - Shi, Gang; Ban, Huiyong; Bai, Yu; Wang, Yuanqing; Luo, Cui; Shi, Yongjiu
Aluminum has been increasingly used in reticulated shell structures for large span applications. The joint configuration in such space structure is essentially important for both architectural and structural performance. A novel cast aluminum joint was introduced in this paper. Full-scale specimens were examined under three loading conditions to study the mechanical performance and failure mechanism. The rotational stiffness, critical sections, and failure modes of the specimens assembled with this novel cast aluminum joint were investigated. Finite element analysis was further performed and validated by the experimental results in order to examine the local stress distributions. Based on the experimental and numerical results, it was found that out-of-plane rotational stiffness of this novel joint was larger than that of in-plane and the joint in both directions was semi-rigid according to Eurocode 3. The cross sections of the joint end and beam end with bolt holes were the critical sections. The comparison of calculated results from elastic FEA and Euler beam theory indicated that reliable safety factors should be considered if the latter is used in design, because of the stress concentration at critical sections.